Use of Cone Beam Computed Tomography in the Assessment of Facial Trauma: Report of Two Cases - Araujo-Silva, Gabriel; Santos-Lima, Cleiton Rone; Ferreira, Guilherme Fantini; Telles-Araújo, Gabriel de Toledo (ARCHIVES OF HEALTH INVESTIGATION, 2024)
Imaging is an essential component in the treatment of facial trauma, as it provides support from diagnosis and treatment planning to the evaluation of results. Cone beam computed tomography (CBCT) enables a tridimensional assessment of anatomical structures. This study aims to evidence, through two case reports of the contribution of CBCT in the diagnosis of facial trauma. In both cases, patients were victims of facial trauma, one due to traffic accidents and the other by fall from height. No type of fracture was verified in emergency medical care. Professionals requested a CBCT exam to assist in the diagnosis of possible fractures. In CBCT images examination, it was possible to visualize foreign bodies in the maxillary region (Case 1), and the presence of mandible fracture (Case 2). The use of CBCT is crucial to obtain details on images that aid the diagnosis of fractures in cases of facial trauma. Even though it is not often used in emergency services, its use is well-indicated for more precise diagnosis.